Incorporating progress monitoring and outcome assessment into counseling and psychotherapy : a primer - Meier, Scott T., 1955- (Oxford University Press, 2014)
"How do therapists know they are making a difference with their clients? Progress monitoring and outcome assessment (PMOA) measures are powerful tools that can provide feedback about short-term progress during counseling and psychotherapy as well as information about the overall amount of progress. Incorporating Progress Monitoring and Outcome Assessment into Counseling and Psychotherapy by Scott T. Meier helps clinicians, students, and researchers learn how to employ and interpret PMOA measures. A new generation of change-sensitive measures has begun to appear that are specially designed to function as PMOA tests. These instruments indicate when a client is not making progress and the mental health professional should consider altering the psychosocial intervention. Research has demonstrated that PMOA measures have the potential to significantly reduce the surprisingly high failure rates found in psychotherapy. Meier describes case studies that incorporate PMOA data, literature relevant to PMOA measurement, and examples of rater training for PMOA measures. Chapters explain how to administer and interpret PMOA data, evaluate the psychometric properties of PMOA measures, understand statistics and graphics employed with PMOA data, and employ PMOA data in supervision. This book will be valuable to mental health providers who use PMOA measures as well as graduate students in clinical, counseling, and school psychology"--